The Right to Extimacy and the Technological-Neoliberal Social Control - Tássia Aparecida Gervasoni; Iuri Bolesina; Felipe da Veiga Dias (Opinión Jurídica)
This research has as its subject the right to extimacy and its relationship with the practices of technological control provided by neoliberal rationality. Based on this, the proposed research problem is: what is lost with the exercise of the right to extimacy in the current techno-neoliberal context? The general objective is focused on determining the affectation of this right and, in the same way, understanding the dimensions that are interconnected through current technological control devices and the domain of neoliberal logics applied to the governmentality of life. To achieve these purposes, we adopted the phenomenological-hermeneutic approach method, which takes as its object of investigation a way of “being in the world”, in which the parameters of the observer are inserted, complemented by the method of monographic procedure and the technique of indirect documentation research with bibliographic emphasis. Based on these considerations, we concluded that spaces for individual, social and democratic construction are lost with the current practices of technological-neoliberal control exercised over extimacy, capturing it as part of the capitalist dynamic and reducing its meaning in the construction of subjectivities in favor of the commodification of life and the precariousness of social relations.